We Used a Double Blind Experiment to Investigate Weak pT-TMS in Epilepsy Patients - ANNINOS, Photios (Maedica (Bucur), 2020)
Magnetoencephalographic recordings, external picoTesla Transcranial Magnetic Stimulation (pT-TMS) and a double blind experimental design were used for the evaluation of 10 epilepsy patients (three males, seven females). Their ages ranged from 23 to 48 years. Our results showed an enhancement in the 2-7 Hz frequency range in five out of nine patients who had a statistically significant difference (55%). The pT-TMS could be a significant means for the treatment of epilepsy. Further research should be done prior to have final conclusions.